2019
DOI: 10.1055/s-0038-1676659
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Polyposis: More than a Chronic Inflammatory Disorder—A Disease of Mechanical Dysfunction—The São Paulo Position

Abstract: Introduction The importance of our study lies in the fact that we have demonstrated the occurrence of mechanical dysfunction within polypoid tissues, which promotes the development of polyps in the nasal cavity. Objective To change the paradigm of nasal polyposis (NP). In this new conception, the chronic nasal inflammatory process that occurs in response to allergies, to pollution, to changes in the epithelial barrier, or to other factors is merely the trigger of the development of the disease in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In this regard, two primary agents are closely involved in tissue mechanical properties: extracellular matrix and cells. The importance of composition of extracellular matrix on nasal polypoid tissues' mechanical properties has been previously demonstrated [10,12,33], but the role of nasal polypoid cells in this mechanical dysfunction continues to remain unclear. In this context, the fibroblasts act in the tissue remodeling and amplification of inflammation through extracellular matrix-cell cross-talking [36,37], act on the pillars of nasal polyp development [38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, two primary agents are closely involved in tissue mechanical properties: extracellular matrix and cells. The importance of composition of extracellular matrix on nasal polypoid tissues' mechanical properties has been previously demonstrated [10,12,33], but the role of nasal polypoid cells in this mechanical dysfunction continues to remain unclear. In this context, the fibroblasts act in the tissue remodeling and amplification of inflammation through extracellular matrix-cell cross-talking [36,37], act on the pillars of nasal polyp development [38].…”
Section: Discussionmentioning
confidence: 99%
“…The lower cellular spreading area combined with a lower traction force on the tissue (and its ability to cause tissue deformation) may share a correlation with the mechanical dysfunction observed in Nasal Polyps. The lower traction force exerted by fibroblast on polypoid tissue has an impact on the interstitial hydrostatic pressure that could significantly favor edema formation and tissue growth in Nasal Polyps [10][11][12]33]. The increase in the interstitial hydrostatic pressure becomes a goal to be achieved to balance the impaired pressure force dynamic found in nasal polyposis that favors the edema formation [10,11,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] This inability to properly elevate interstitial hydrostatic pressure in the polypoid nasal mucosa is closely related to the unique makeup of its extracellular matrix, which develops as the result of an anomalous tissue remodeling process. 4,5 In this context, transforming growth factor beta 1 (TGFβ-1) plays a pivotal role in the remodeling process of abnormal tissue in cases of NP. [6][7][8][9] In a previous study, 10 we demonstrated that fibroblasts isolated from patients with chronic rhinosinusitis without NP exhibit increased matrix metalloproteinase 1 (MMP1) and cysteinyl leukotriene receptor 1 (CysLTR1) after stimulation with leukotriene D4 (LTD4), with an additional increase occurring in the presence of TGF-β1.…”
Section: Introductionmentioning
confidence: 99%